Fringing reef growth in the Mid-Devonian: an example from the southern Rhenish Massif, Germany - Königshof, Peter; Flick, Heiner (Palaeobiodiversity and Palaeoenvironments, 2023)
The Givetian Balduinstein Reef developed upon mixed felsic lavas and volcaniclastic tuffs. The Givetian age of the reef is proven by conodonts (Polygnathus rhenanus/varcus Zone to the Polygnathus ansatus Zone) and the occurrence of the brachiopod Stringocephalus burtini. Remains of land plants and subaerially ejected volcanic bombs in the vicinity of the outcrops document that the volcano was an emerged island surrounded by a fringing reef in an unstable tectonic environment. Reef development is characterised by a complex interaction of volcanism, erosion and the rate and pattern of sea-level change, which resulted in a variety of facies settings and rock-types. Microfacies analysis and rock-types prove that the fringing reef was backed by a shallow lagoon. A lime mudstone/alkali rhyolitic breccia represents a lava flow, or more probably a dome collapse breccia, which flowed into the lagoonal mud and confirms a contemporaneous occurrence of volcanism and reef growth. Reefs flourished during several episodes of inactivity of the volcano, particularly in the upper part of the sections, suggesting that the reef development kept up with sea-level changes and/or local events. Lithofacies of the upper part of the youngest section point to a regressive phase. The distinctive depositional architecture and evolution of the Balduinstein Reef are interpreted as having been controlled mainly by regional tectonics and volcanism with contributions from eustasy.